60Co irradiation grafting modified polyvinyl chloride latex and preparation method thereof

Through 60Co irradiation grafting modified polyvinyl chloride latex, the problems of high process difficulty, low comonomer components and poor product performance in the prior art are solved, and efficient modification of polyvinyl chloride latex is achieved. The product has excellent film forming performance and flame retardant self-extinguishing performance, meeting the requirements of water-based coatings and water-based adhesives.

CN119708366APending Publication Date: 2025-03-28GNSG ANHUI HONG SIFANG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411811883.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, when preparing polyvinyl chloride copolymers, the process difficulty is high, the comonomer components are low, and the product performance is poor, and the requirements of water-based coatings and water-based adhesives are not met.

Method used

The modified polyvinyl chloride latex is grafted by 60Co irradiation, and the polyvinyl chloride molecular chain is degraded and then bonded to the comonomer by 60Co irradiation, achieving efficient modification of the copolymer.

Benefits of technology

The content of comonomer components is improved, the residue of initiators and catalysts is reduced, the reaction conditions are mild, the product has excellent low-temperature film formation performance and flame retardant self-extinguishing performance, meeting the use requirements of water-based coatings and water-based adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708366A_ABST
    Figure CN119708366A_ABST
Patent Text Reader

Abstract

The invention provides 60Co irradiation grafting modified polyvinyl chloride latex and a preparation method thereof, and relates to the technical field of high polymer materials, the latex comprises the following components by weight: 900-1100 g of polyvinyl chloride latex, 200-450 g of a comonomer, 4-6 g of an emulsifier, and 110-130 g of deionized water, the raw materials are mixed to form a pre-emulsion, and the pre-emulsion is subjected to 60Co irradiation grafting; the preparation method comprises the following steps: blending the deionized water, the comonomer, the emulsifier and the polyvinyl chloride latex, stirring and emulsifying to obtain a pre-emulsion; and irradiating the pre-emulsified liquid by using 60Co to obtain the grafted modified polyvinyl chloride latex. The method is not limited by reactivity, the content of comonomer components can be adjusted according to requirements, and the performance of the copolymer is achieved to the maximum extent; according to the preparation method, the reaction condition is mild, the reaction process is easy to control, polyvinyl chloride molecular chains can be degraded to a certain extent through 60Co irradiation, then comonomers are bonded, chemical bonding is achieved on a core-shell interface, the stability of a copolymer is improved, and the film forming performance of a product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a 60 Co irradiation grafted modified polyvinyl chloride latex and preparation method thereof. Background Art

[0002] Polyvinyl chloride is one of the four general-purpose synthetic resins, with excellent flame retardancy, wear resistance, chemical corrosion resistance and water vapor barrier properties. Polyvinyl chloride materials have excellent comprehensive mechanical properties, and their products have high transparency, electrical insulation, heat insulation, sound absorption and shock absorption. It is the most cost-effective general-purpose material and is very suitable for use as water-based coatings. However, due to the shortcomings of polyvinyl chloride in terms of thermal stability, impact resistance and weather resistance, the notched impact strength of rigid polyvinyl chloride materials is only 3-5kJ / m 2 , which is a hard and brittle material; while the soft polyvinyl chloride material has a prominent problem of plasticizer migration due to the addition of a high proportion of plasticizers, and is prone to brittle cracking and peeling during use. At the same time, due to the strong interaction between molecular chains, the relative sliding of molecules is difficult, the melt viscosity is large and the fluidity is poor. In addition, homopolymer polyvinyl chloride has poor solubility in low-polarity solvents, weak substrate adhesion, and cannot form a film at low temperatures. The above problems seriously limit its application in the field of water-based coatings and water-based adhesives.

[0003] The above problems can currently be solved by copolymerization. The polymerization reaction of vinyl chloride is a free radical polymerization, and the composition of the comonomer in the polymer molecular chain depends largely on the monomer concentration and the polymerization activity of the monomer. Due to the huge difference in the reactivity rate between vinyl chloride and most monomers, it is difficult to achieve uniform copolymerization. At present, most of the vinyl chloride copolymerization methods have two methods: one is to use a two-step method, that is, first prepare a polyvinyl chloride homopolymer latex, and then polymerize the comonomer for a secondary polymerization; the other is direct copolymerization, that is, the vinyl chloride monomer and the comonomer are polymerized in one step to generate a copolymer latex. In the two-step method, polyvinyl chloride is not actually copolymerized, but simply physically coated. Although the "shell" layer can achieve low-temperature film formation, the "core" layer is still a polyvinyl chloride homopolymer and cannot form a film at low temperature. After the film is formed, internal stress will be generated between the core and shell of the material, resulting in a non-dense film. The mechanical properties of the membrane material are greatly reduced and the copolymerization performance cannot be reflected. Due to the competitive polymerization rate, direct copolymerization is usually achieved by increasing the concentration of vinyl chloride monomer and reducing the concentration of comonomer. This not only leads to very low content of other copolymer components in the copolymer and cannot fully reflect the performance of the comonomer, but also has extremely high requirements on the control process of the polymerization process. The product can only be used as a modified additive and cannot meet the requirements of water-based coatings and water-based adhesives. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] In view of the deficiencies in the prior art, the present invention provides a 60Co irradiation graft modified polyvinyl chloride latex and its preparation method solve the technical problems of high process difficulty, low copolymer monomer component and poor product performance that cannot meet the use requirements in the prior art preparation process.

[0006] (II) Technical solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] 60 Co irradiation graft modified polyvinyl chloride latex, comprising the following components in parts by weight: 900-1100g of polyvinyl chloride latex, 200-450g of comonomer, 4-6g of emulsifier, 110-130g of deionized water, the above raw materials are mixed into a pre-emulsified liquid for use 60 Co irradiation grafting.

[0009] Preferably, the comonomer includes a mixture of one or more of acrylic acid and its ester monomers, amide monomers, and styrene monomers.

[0010] Preferably, the acrylic acid and its ester monomers are a combination of butyl acrylate, methyl methacrylate, methyl acrylate, isooctyl acrylate, methacrylic acid, isopentyl acrylate, butyl methacrylate, glycidyl acrylate, hydroxyethyl acrylate, and acrylic acid;

[0011] Preferably, the amide monomer is hydroxymethyl acrylamide or acrylamide.

[0012] Preferably, the composition comprises the following components in parts by weight: 900-1100g of polyvinyl chloride latex, 200-300g of butyl acrylate, 3-6g of acrylic acid, 0-20g of amide monomer, 0-50g of isooctyl acrylate, 0-50g of styrene monomer, 0-3g of methacrylic acid, 0-10g of methyl methacrylate, 4-6g of emulsifier, and 110-130g of deionized water. The above raw materials are mixed into a pre-emulsified liquid for use. 60 Co irradiation grafting.

[0013] Preferably, the emulsifier is one or a combination of sodium cetyl betaine, potassium laurate, alkylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate, polyoxyethylene alkyl ester, sodium dodecyl sulfate, polyoxyethylene alkyl aryl ester.

[0014] Preferably, the polyvinyl chloride latex is obtained by emulsion polymerization of vinyl chloride, and the solid content of the polyvinyl chloride latex is 35±5%, and the particle size is 80-200 nm.

[0015] 60 The preparation method of Co irradiation grafted modified polyvinyl chloride latex specifically comprises the following steps:

[0016] Step 1: blend deionized water, comonomer, emulsifier and polyvinyl chloride latex, and stir and emulsify to obtain a pre-emulsion.

[0017] Step 2: Use 60 The pre-emulsion was irradiated with Co to obtain grafted modified polyvinyl chloride latex.

[0018] Preferably, the specific method of step 1 is: adding the emulsifier into deionized water under stirring, then adding the comonomer into the blend of the emulsifier and deionized water, stirring evenly, and finally adding the polyvinyl chloride latex, stirring and emulsifying to obtain a pre-emulsion.

[0019] Preferably, the 60 The Co irradiation dose is 1 kGy-30 kGy, and the irradiation dose rate is 100 Gy / h-10000 Gy / h.

[0020] Preferably, the 60 The Co irradiation dose is 5kGy-20kGy, and the irradiation dose rate is 500Gy / h-5000Gy / h.

[0021] Preferably, the solid content of the radiation grafted modified polyvinyl chloride latex is 50±10%.

[0022] Preferably, the polyvinyl chloride content in the solid content of the radiation grafted modified polyvinyl chloride latex is 10%-70%.

[0023] (III) Beneficial effects

[0024] The present invention provides a 60 Co irradiation grafted modified polyvinyl chloride latex and its preparation method. Compared with the prior art, it has the following beneficial effects:

[0025] 1. The present invention is not limited by the reactivity ratio, and the content of the comonomer component can be adjusted according to demand, and the performance of the copolymer can be achieved to the greatest extent;

[0026] 2. The present invention does not require initiators and catalysts, which reduces the residues of initiators and catalysts in the finished product and makes the product purer;

[0027] 3. The preparation method of the present invention can realize polymerization reaction under normal temperature and pressure, the reaction conditions are mild, and the reaction process is easy to control;

[0028] 4. The present invention is not a simple physical coating "core-shell" structure. 60 Co irradiation can degrade the polyvinyl chloride molecular chains in polyvinyl chloride latex to a certain extent and then bond with the copolymer monomers. The "core-shell" interface can achieve a certain degree of chemical bonding, which improves the stability of the copolymer and enhances the film-forming properties of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 The corresponding photos of the film formation and water whitening resistance of the emulsion obtained in Example 3 and the water whitening resistance recovery status are shown;

[0031] Figure 2 The corresponding photos of the film formation and water whitening resistance of the emulsion obtained in Example 9 and the water whitening resistance recovery status are shown;

[0032] Figure 1 , Figure 2 ① shows a wet film photo made with a 100μm film-making device;

[0033] ② shows the photo of ① after it was placed in a 50℃ drying oven for 30 minutes and then taken out and placed at room temperature;

[0034] ③ shows a photo of ② after it was placed at room temperature for 24 hours and then immersed in tap water for 48 hours (the tap water covered 1 / 5 to 1 / 3 of the membrane);

[0035] ④ is a photograph of ③ after being placed at room temperature for 48 hours. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The present invention provides a 60 Co irradiation grafting modified polyvinyl chloride latex and preparation method thereof. The irradiation grafting modified polyvinyl chloride latex prepared by the method not only has the components of the comonomer significantly improved, but also has the reaction process that is easy to control and the reaction conditions are mild. The product not only has excellent low-temperature film-forming properties, but also has certain flame retardant and self-extinguishing properties, and can meet the use requirements of water-based coatings and water-based adhesives.

[0038] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0039] The emulsifier of the present invention is one or a combination of sodium cetyl betaine, potassium laurate, alkylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate, polyoxyethylene alkyl ester, sodium dodecyl sulfate, and polyoxyethylene alkyl aryl ester.

[0040] The polyvinyl chloride latex used in the following Table 1 is obtained by emulsion polymerization of vinyl chloride, and the relevant parameters of the polyvinyl chloride latex are: solid content 35±5%, pH 9-11, median particle size (D50) 80-200nm, and the polyvinyl chloride latex used in Examples 1-9 in Table 1 is the same.

[0041] Examples 1-9

[0042] 60 The Co irradiation grafted modified polyvinyl chloride latex specifically comprises the following components in parts by weight:

[0043] Table 1 - Specific ingredients of radiation grafted modified polyvinyl chloride latex of Examples 1-9

[0044]

[0045] Embodiment 10:

[0046] 60 The preparation method of Co irradiation grafted modified polyvinyl chloride latex specifically comprises the following steps:

[0047] Step 1, add deionized water into a suitable container, add the emulsifier into the container under mechanical stirring (high-speed disperser, speed 800rpm), and stir evenly;

[0048] Step 2, adding the raw materials numbered 2-8 in Example 1-9 into a container, and continuing stirring for 10-15 minutes;

[0049] Step 3, adding polyvinyl chloride latex into the container, and continuing stirring for 5-10 minutes to obtain a pre-emulsion;

[0050] Step 4: Pour the pre-emulsion into a glass kettle with a stainless steel paddle stirrer and add 60 The irradiation was performed using a Co irradiation device, the irradiation dose rate was 1000 Gy / h, the irradiation dose was 8 kGy, the stirring speed during the irradiation process was 200 rpm, and after the irradiation was completed, a milky white emulsion was taken out to obtain;

[0051] Step 5: adjusting the pH of the milky white emulsion to 7.5-8.0 with 18% ammonia water, and filtering to obtain the finished product.

[0052] Performance testing:

[0053] In combination with Examples 1-10, the prepared finished products were tested for performance, and the test results are shown in Table 2.

[0054] Table 2 - Finished product performance test results

[0055]

[0056]

[0057] In order to achieve polymerization smoothly, the quantitative amount of polyvinyl chloride latex in the polymerization formula in Table 1 remains unchanged. The minimum film-forming temperature of the polymer and the water resistance after film formation are adjusted by adjusting the addition amount of the remaining raw materials. The minimum film-forming temperature is achieved by adjusting raw materials 1-8, and the water resistance is achieved by adjusting raw materials 1-8 and raw material 9.

[0058] It can be seen from the test data of Table 2, especially the 5th and 6th items, that raw materials 3, 4 and 7 can all improve the viscosity of the finished product, and the synergistic cooperation of raw materials 3 and 4 can improve the stability of the system during the polymerization process. Specifically, it can be seen that in Examples 1, 2 and 5, raw material 4 acrylamide is not added, and the stability of the finished product is not as good as the effect of the synergistic cooperation of raw materials 3 and raw materials 4. Compared with Example 1 and Example 5, the demulsification degree of Example 2 is lighter, which may be related to the effect of synergistically improving the stability of the addition of styrene in Example 2, and may also be related to the counter-effect of the addition of isooctyl acrylate in Examples 1 and 5. Excessive addition of raw materials 3 and 4 will affect the water resistance of film formation, which all shows to a certain extent that the selection of raw materials and the ratio of raw materials determine the strength of the synergistic effect between raw materials. The synergistic cooperation of raw materials 3 and raw materials 7 can improve the water resistance of the product to a certain extent, but the stability of the polymerization system will decrease, which is reflected in the stability test results of Example 5. It can be seen from this that when raw materials 3, 4 and 7 are coordinated, the system stability and water resistance are the best.

[0059] Raw materials 2 and 5 are soft monomers, and the synergistic cooperation of the two can achieve low-temperature film formation of the product.

[0060] Raw materials 3, 4, 6-8 are hard monomers. By adjusting the addition ratio of soft and hard monomers, the lowest film-forming temperature of the finished product can be adjusted to meet the actual production requirements. Among the soft monomers, the hydrophilicity of raw material 2 is stronger than that of raw material 5; among the hard monomers, the hydrophilicity of raw materials 3, 4 and 6 is stronger than that of raw materials 7 and 8.

[0061] Raw material 8 is used to emulsify raw material 2-7. When raw material 8 cooperates with several of raw materials 2-7, raw material 2-7 can be evenly dispersed into a micellar liquid before polymerization, which is beneficial to the system stability of the polymerization process. Within a certain range, if raw material 2-8 is added in large amounts, the particle size of the finished product can be reduced, which is beneficial to the system stability of the polymerization process, but the water resistance will be reduced to a certain extent; if raw material 2-8 is added in small amounts, the particle size of the finished product will increase to a certain extent, which is not conducive to the system stability of the polymerization process, but the water resistance of the finished product will be improved to a certain extent. Therefore, the addition ratio of raw material 2-8 needs to be controlled within a reasonable range to maximize product performance.

[0062] From the test data in Table 2, it can be seen that the median particle size of the latex obtained in Example 8 is the largest, the latex appearance is white, and the water resistance is slightly poor; the latex obtained in Examples 1-3 and Example 5 has low viscosity; the lowest film-forming temperature of the latex obtained in Examples 1, 4, 5 and 8 is low, which is suitable for adhesives; the film-forming temperature of the latex obtained in Examples 2, 3, 6, 7 and 9 is close to room temperature, which is suitable for water-based coatings. Combining the solid content, viscosity, film temperature and water whitening resistance results, the latex obtained in Example 3 is more suitable for adhesives; the latex obtained in Example 9 is more suitable for water-based coatings.

[0063] The corresponding emulsion film formation and water whitening resistance photos and water whitening resistance recovery photos of Example 3 are as follows Figure 1 Example 9 corresponds to the obtained emulsion film and water whitening photos and water whitening recovery photos as shown Figure 2 It can be seen that the films of Example 3 and Example 9 are uniform, showing different degrees of blue and white after being soaked in water, and the films after being soaked in water can basically recover to the state before being soaked in water (careful observation can reveal very slight traces of soaking in water, which is a normal phenomenon).

[0064] In summary, compared with the prior art, the present invention has the following beneficial effects:

[0065] 1. The present invention is not limited by the reactivity ratio, and the content of the comonomer component can be adjusted according to demand, and the performance of the copolymer can be achieved to the greatest extent;

[0066] 2. The present invention does not require initiators and catalysts, which reduces the residues of initiators and catalysts in the finished product and makes the product purer;

[0067] 3. The preparation method of the present invention can realize polymerization reaction under normal temperature and pressure, the reaction conditions are mild, and the reaction process is easy to control;

[0068] 4. The present invention is not a simple physical coating "core-shell" structure. 60Co irradiation can degrade the polyvinyl chloride molecular chains in polyvinyl chloride latex to a certain extent and then bond with the copolymer monomers. The "core-shell" interface can achieve a certain degree of chemical bonding, which improves the stability of the copolymer and enhances the film-forming properties of the product.

[0069] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0070] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. 60 Co irradiation graft modified polyvinyl chloride latex, characterized in that: The composition comprises the following components by weight: 900-1100g of polyvinyl chloride latex, 200-450g of comonomer, 4-6g of emulsifier, and 110-130g of deionized water. The above raw materials are mixed into a pre-emulsified liquid for use. 60 Co irradiation grafting.

2. The method according to claim 1 60 Co irradiation graft modified polyvinyl chloride latex, characterized in that: The comonomer includes a mixture of one or more of acrylic acid and its ester monomers, amide monomers, and styrene monomers.

3. The method according to claim 2 60 Co irradiation graft modified polyvinyl chloride latex, characterized in that: The acrylic acid and its ester monomers are various combinations of butyl acrylate, methyl methacrylate, methyl acrylate, isooctyl acrylate, methacrylic acid, isopentyl acrylate, butyl methacrylate, glycidyl acrylate, hydroxyethyl acrylate, and acrylic acid; The amide monomer is hydroxymethyl acrylamide or acrylamide.

4. The method according to claim 3 60 Co irradiation graft modified polyvinyl chloride latex, characterized in that: The invention comprises the following components in parts by weight: 900-1100g of polyvinyl chloride latex, 200-300g of butyl acrylate, 3-6g of acrylic acid, 0-20g of amide monomer, 0-50g of isooctyl acrylate, 0-50g of styrene monomer, 0-3g of methacrylic acid, 0-10g of methyl methacrylate, 4-6g of emulsifier, and 110-130g of deionized water. The above raw materials are mixed into a pre-emulsified liquid for use. 60 Co irradiation grafting.

5. The method according to claim 1 60 Co irradiation graft modified polyvinyl chloride latex, characterized in that: The emulsifier is one or a combination of sodium cetyl betaine, potassium laurate, alkylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate, polyoxyethylene alkyl ester, sodium dodecyl sulfate, and polyoxyethylene alkyl aryl ester.

6. The method according to claim 1 60 Co irradiation graft modified polyvinyl chloride latex, characterized in that: The polyvinyl chloride latex is obtained by emulsion polymerization of vinyl chloride, has a solid content of 35±5%, and a particle size of 80-200 nm.

7. The method according to any one of claims 1 to 6 60 The method for preparing Co irradiation grafted modified polyvinyl chloride latex is characterized in that: The specific steps include: Step 1, blending deionized water, comonomer, emulsifier and polyvinyl chloride latex, stirring and emulsifying to obtain a pre-emulsion; Step 2: Use 60 The pre-emulsion was irradiated with Co to obtain grafted modified polyvinyl chloride latex.

8. The method according to claim 1 60 The method for preparing Co irradiation graft modified polyvinyl chloride latex is characterized in that: The specific method of step one is: adding the emulsifier into deionized water under stirring, then adding the comonomer into the blend of the emulsifier and deionized water, stirring evenly, and finally adding the polyvinyl chloride latex, stirring and emulsifying to obtain a pre-emulsion.

9. The method according to claim 1 60 The method for preparing Co irradiation grafted modified polyvinyl chloride latex is characterized in that: Said 60 The Co irradiation dose is 1 kGy-30 kGy, the irradiation dose rate is 100 Gy / h-10000 Gy / h, the solid content of the irradiation grafted modified polyvinyl chloride latex is 50±10%, and the polyvinyl chloride content in the solid part of the irradiation grafted modified polyvinyl chloride latex is 10%-70%.

10. The method according to claim 9 60 The method for preparing Co irradiation graft modified polyvinyl chloride latex is characterized in that: Said 60 The Co irradiation dose is 5kGy-20kGy, and the irradiation dose rate is 500Gy / h-5000Gy / h.